2019
DOI: 10.1088/1361-6404/aaf661
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of physics students’ problem solutions: calculating the work done by a three-dimensional conservative force field

Abstract: The aim of this study is to analyze physics students’ problem solutions related to calculus-based physics problems. The sample of this study consists of 41 third-year university students studying in a physics education program. Two physics problems were posed to the students in the study. The students’ problem solutions were analyzed descriptively. According to one of the results obtained from the study, most of the students calculated the curl of the force field and proved whether it is conservative or not. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…d) Conceptual learning and problem solving: six studies investigated gender differences in the conceptual learning and problem solving of physics topics. Studies showed no significant statistical difference between male and female performance in relation, for example, to solutions of calculus-based force problems (Gülçiçek, 2019) or to the learning of magnetism concepts (Li & Singh, 2017). The teaching of Einsteinian concepts to middle school students showed to increase girls' scores in physics (Kaur et al, 2017).…”
Section: Gender Differencesmentioning
confidence: 93%
“…d) Conceptual learning and problem solving: six studies investigated gender differences in the conceptual learning and problem solving of physics topics. Studies showed no significant statistical difference between male and female performance in relation, for example, to solutions of calculus-based force problems (Gülçiçek, 2019) or to the learning of magnetism concepts (Li & Singh, 2017). The teaching of Einsteinian concepts to middle school students showed to increase girls' scores in physics (Kaur et al, 2017).…”
Section: Gender Differencesmentioning
confidence: 93%
“…d) Aprendizagem conceitual e resolução de problemas: seis estudos investigaram diferenças de gênero na aprendizagem conceitual e resolução de problemas de tópicos de física. Os estudos não mostraram diferença estatística significativa entre o desempenho masculino e feminino em relação, por exemplo, às soluções de problemas de força baseados em cálculo (Gülçiçek, 2019) ou ao aprendizado de conceitos de magnetismo (Li & Singh, 2017). O ensino de conceitos einsteinianos para alunos do ensino médio mostrou aumentar as notas das meninas em física (Kaur et al, 2017).…”
Section: Diferenças De Gênerounclassified